The professional socialization of the graduate assistant athletic trainer - Mazerolle, S. M.; Eason, C. M.; Clines, S.; Pitney, W. A. (Journal of Athletic Training, 2015)
Context: The graduate assistant athletic trainer (AT) position often serves as one's first experience working independently as an AT and is also an important aspect of the professional socialization process. The socialization experiences of graduate assistant ATs have yet to be fully explored.